Strategic opportunities for Islamic finance: the French legal framework for venture capital and cooperative finance - Oseni, Umar Aimhanosi; Matri, Dorsaf (2014)
Venture capital is an effective tool for investment in both early stage and hi-tech businesses. From a purely legalistic perspective, this paper examines the current legal framework of France on venture capital and the opportunities it presents for shari‘a-compliant investments. The study adopts an analytical approach in dissecting the relevant laws and regulations, including the relevant European Union Directives and Regulations, on venture capital in France and explores salient provisions through content analysis for possibilities of introducing shari‘a-compliant venture capital operations in the country. While focusing only on the legal framework on venture capital in France and the Islamic venture capital models, this study does not intend to dwell in the regulatory framework of other sectors of the French financial system. The findings of this study would provide a clear direction, which includes the opportunities and inevitable risks, for investors who are willing to venture into the French investment arena using the Islamic venture capital instruments. Though few studies have been carried out on potentials of Islamic finance in France generally, there has not been much focus on venture capital sector which might give a new impetus to efforts toward building bridges across financial communities. The paper concludes that, with some glaring connections with Islamic law, the French legal framework on venture capital has the potentials of accommodating shari‘a-compliant venture capital operations.